The Effect of Artificial Accelerated Aging on The Color of Ceramic Veneers Cemented With Different Resin Cements (A Comparative In Vitro Study) - Hussain, Shatha Kh.; Al-Rawi, Inas I. (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Color changes that are detectable to human eye can affect the esthetic appearance of ceramic veneers. The purpose of this study was to evaluate and compare the effect of artificial accelerated aging on the color of ceramic veneers cemented with different resin cements.Materials and Methods: Sixty discs were prepared with 0.5 mm thickness, 30 discs made from IPS e.max press (Ivoclar Vivadent) and 30 discs were made from VITA Enamic (VITA Zahnfabrik). The discs were cemented with three resin cements: Variolink Veneer MV 0 shade (Ivoclar Vivadent), Rely X veneer Translucent shade (3M ESPE) and NX3 Nexus Clear shade (Kerr Corporation) with 0.1 mm thickness. The spectrophotometer Easyshade Advance was used to measure the color parameters (Lightness, axis a* of chroma and axis b*of chroma) immediately after cementation, after 150 and 300 hours of aging. The specimens were subjected to artificial accelerated aging in Accelerated Weathering Tester. Color change greater than 3.3 was considered unacceptable. One-way ANOVA, paired t-tests and Bonferroni adjusted t-test were used for statistical analysis (p